Analysis Of The 2nd Principle Of Pancasila On The Instagram Privacy Disclaimer - Dwipasari, Berlian; Ananta Saputra, Nicolas; Thalib, Emmy Febriani (Journal of Digital Law and Policy, 2024)
The article discusses the importance of user privacy on Instagram, a popular social media platform. In the digital era, millions of users share aspects of their personal lives, creating risks of data misuse and security threats. The right to privacy is recognized as a human right, including in the Indonesian Privacy Rights Law. Privacy Controls: Instagram gives users full control, allowing personal account settings. Data Policy: Instagram has a policy that explains the collection, use, and sharing of data, reflecting civilized principles. Data Security: Instagram claims to implement security measures and collaborate with third parties. Privacy Tools and Features: Instagram is constantly developing new privacy tools and features. In the context of Instagram user privacy, the principle of the 2nd Principle, "Just and Civilized Humanity," reflects fair treatment and respect for human rights. The rights to privacy, freedom of expression, data security, and control over personal information are the emphasis in implementing the 2nd Principle. Assessing the use of Instagram's privacy policy by the 2nd Principle and encouraging users to be wise in sharing information. A mixed method approach with descriptive qualitative methods and literature studies is used to understand the impact of Instagram user privacy. Privacy is a human right, and Instagram is expected to implement the principles of the 2nd Principle with policies that support the control, security, and fair treatment of users' data.